SOMEONE BETWEEN: ETHICAL AND MEDICAL PROBLEMS OF HUMAN AND (NON)HUMAN ANIMAL ENHANCEMENT - ŻOK, AGNIESZKA; BAUM, EWA (Society Register, 2019)
Human dreams of a long and healthy life are becoming increasingly real. The advancement of medical technology allows to modify the genome or personalised therapy in order to avoid troublesome side effects. This process also leads to the blurring of boundaries between humans and animals. Rats with induced human diseases are used for testing drugs for incurable illness; humanised pigs can donate organs that are compatible with the genome and immune system of the recipient. A brave new human is approaching, and new “human” animals are making this possible. The main objective of the article is to show the differences between the refinement of people and other animals and to analyse this phenomenon from an ethical point of view.